Proceedings of the Third International Symposium on Automated Composites Manufacturing - Hoa, S. V. (DEStech Publications, Inc., 2017)
The proceedings of the Third International Symposium on Automated Composites Manufacturing contain 29 papers that were presented at the Symposium. A good number of papers deal with new methods for heating, and new methods for the inspection of the quality of the laminates as they are laid. Dry fibers and special laminates and structures deriving from automation have been investigated. There are also new developments in draping, stamp forming, braiding and weaving. There is also work on simulation of the process and subsequent material behavior--pages ix-x.
Keywords: Composite materials -- Congresses.; elektronické knihy; electronic books